(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To evaluate the effectiveness of LASER acupuncture combined with acupressure massage therapy (AMT) in the treatment of cervical pain caused by cervical spondylosis; to investigate the clinical adverse effects of this combined method. Subjects and methods: This was an open-label interventional clinical study with pre- and post-treatment comparisons and a control group. A total of 60 patients diagnosed with cervical pain due to cervical spondylosis were enrolled and divided into two groups: the study group received LASER acupuncture combined with AMT over a 20-day period; the control group received AMT alone for 20 days, from May 2024 to February 2025. Results: After 20 days of treatment, the mean VAS score in the study group was 0.57 compared to 1.07 in the control group; the VAS improvement efficiency was 3.86 in the study group versus 3.43 in the control group. Cervical range of motion improved significantly more in the study group than in the control group (p < 0.05). The NDI improvement was 20.27 points in the study group and 16.4 points in the control group. Overall treatment outcomes after 20 days showed: in the study group: good in 53.3% and fair in 46.7%; in the control group: good in 10% and fair in 90%. Conclusion: LASER acupuncture combined with acupressure massage therapy is effective in treating cervical pain due to cervical spondylosis, as demonstrated by improvements in mean VAS score, cervical range of motion, and NDI functional score. No adverse events or side effects were reported among study participants.